Left atrial reservoir strain is an independent prognostic predictor in patients undergoing percutaneous mitral valve repair. (4th February 2022) - Galli, E; Hubert, P; Vely, M; Panis, V; L"official, G; Donal, E
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Left atrial reservoir strain (LARS) is a well-known prognostic predictor in several cardiac diseases. Aim of the presence study was to assess the value of LARS in predicting the occurrence of major adverse cardiovascular events (MACEs) in patients undergoing percutaneous mitral valve repair (PMVR) Methods and results: 112 patients (62% males, age: 74 ± 10 years) undergoing PMVR for severe primary (n = 71, 63%) or secondary MR were retrospectively included in the study underwent a comprehensive echocardiography before the procedure. Thirty-eight MACES occurred during a median follow-up of 18 months. At multivariable Cox-regression analysis, ischemic cardiomyopathy [HR 2.41 (1.11-5.24, p = 0.02)], indexed left atrial volume [HR 1.01 (1.00-1.01), p = 0.03], and LARS [HR 0.93 (0.88-0.99), p = 0.03] were all significant predictors of MACEs. A cut-off of 13% for LARS (AUC 0.66, p = 0.008) was able to predict MACEs with a 71% sensitivity and 41% specificity (Table 1). Conclusions: LARS is an independent predictor of MACEs in patients undergoing percutaneous mitral valve repair, independently of the etiology of mitral regurgitation.